A history of Adivasi women in post-independence Eastern India : the margins of the marginals - De, Debasree
A history of the historyless, and the marginalization of adivasi voices. A History of Adivasi Women in Post-Independence Eastern India is a path-breaking book that explores the current status of adivasi women in the four states of eastern India with high percentages of adivasis--Bihar, Jharkhand, Odisha and West Bengal. Debasree De engages with the recent paradigm of 'development and displacement' and adivasi women's marginalization and cultural silencing. The findings in the book are based on extensive field surveys in teagardens, stone crushing sites, brick kilns and construction industries. Further, the book provides new material on the extremist villages of Jangal Mahal, Koraput, Malkangiri and Niyamgiri Hills. Linking tribe and gender, the author elaborates how forest economy is women's economy; forcible eviction by multinationals for new industries has led to severe displacement and poverty, apart from intensification of witch hunting and trafficking of girls.